Prevalence of Psychoactive Substance Use Among Nigerian Male Commercial Vehicle Drivers Selected from The Three Major Ethnic Groups in Nigeria - Tochukwu Frank Egwuatu; Onyekachi Ogbonnaya Iroanya; Khalid Olajide Adekoya (Biology, Medicine, & Natural Product Chemistry, 2020)
The use of psychoactive substances for several reasons by commercial vehicle drivers has been documented as a major cause of increased incidences of traffic accidents globally. The study aimed at determining the prevalence of psychoactive substance use among Nigerian male commercial vehicle drivers randomly selected from the three major ethnic groups in Nigeria (Igbo, Hausa and Yoruba). A structured questionnaire which included data on sociodemographic status and psychoactive drug use history was introduced to all participants. Generic Multi-Drug Urine Dip Card Test Kit and Shimadzu chromatograph system (Shimadzu Corporation, Kyoto, Japan) were used for toxicological analyses. Out of the 264 Nigerian male commercial vehicle drivers who participated in this study, 111(42.0 %) had used illicit drugs in recent times, 55(20.8 %) took drugs for improved energy and 90(34.1 %) felt high after using illicit drugs. Marijuana was the most abused substance; 77(29.2 %) followed by benzodiazepine; 34(12.9) across all ethnicities studied. Across all ethnicities, HPLC revealed that the Hausa drivers had the highest concentration of psychoactive substances in their urine samples. These findings, reiterates the need for the Nigerian anti-drug agency to develop new strategies in conducting a repressive drug war and extending the same to bus stations.